Oral Microbial Communities and Oral Health - Nomura, Yoshiaki (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
More than 700 species of bacteria are involved in the oral cavity. Specific pathogenic bacteria have been focused on as pathogenic bacteria for oral disease: dental caries and periodontal disease. However, these pathogenic bacteria occupy a tiny fraction of the overall oral microbiome. A high throughput genomic analysis system was developed. This technology innovation enables analysis of the whole bacteria. It is hypothesized that disturbance of the oral microbiome, so-called dysbiosis, leads to the development of some diseases. This book provides knowledge concerning recent advances in the oral microbiome for researchers as well as dental clinicians.